Blood donations and incentives: Evidence from a field experiment - Lorenz Götte; Alois Stutzer (University of Basel, Center of Business and Economics (WWZ), 2019)
There is a longstanding concern that material rewards might undermine pro-social motivations, thereby leading to a decrease in blood donations. This paper provides an empirical test of how material rewards affect blood donations in a three-month large-scale field experiment and a fifteen-month follow-up period, involving more than 10,000 previous donors. We examine the efficacy of a lottery ticket as a reward vis-à-vis a standard invitation, an appeal, and a free cholesterol test. The offer of a lottery ticket, on average, increases the probability to donate blood during the experiment by 5.6 percentage points over a baseline donation rate of 46 percent. We find that this effect is driven by less motivated donors. Moreover, no reduction in donations is observed after the experiment.
Keywords: C93; D64; H41; I18; 330; blood donations; field experiment; material rewards; motivation crowding effect; pro-social behavior